Electrophysiological and metabolic characterization of single beta-cells and islets from diabetic GK rats. - Hughes, S; Faehling, M; Thorneley, C; Proks, P; Ashcroft, F; Smith, P (1998)
We have used the whole-cell recording technique to determine whether ATP-sensitive potassium (K[ATP]) currents, voltage-dependent Ca2+ currents, and exocytosis are different in single beta-cells from pancreatic islets of Goto-Kakizaki (GK) rats, a novel model of NIDDM, and normal rats. In addition, we have also measured the insulin secretory responses, ATP content, and the rate of glucose metabolism in intact islets. Although the glucose sensitivity of the K(ATP) current was similar between GK rats and controls, in the absence of glucose, K(ATP) current density was larger in GK rats, which resulted in a more hyperpolarized membrane potential. Whole-cell Ca2+ currents were similar. By monitoring the cell capacitance with a fixed intracellular solution, no difference was detected in the exocytotic responses of beta-cells from normal and GK rats. In islets from GK rats, the rates of glucose utilization ([3H]H2O production from 5-[3H]glucose) and oxidation ([14C]CO2 production from U-[14C]glucose) were not significantly different from controls. Insulin secretion, however, was impaired (by 50%), and this was paralleled by a smaller increase in ATP content in response to stimulation by 10 mmol/l glucose in islets from GK rats when compared with controls. Under conditions in which K(ATP) channels were held open and the effects of glucose were independent of membrane potential, insulin release was still significantly lower in GK rat islets than in controls. These findings suggest that the impaired insulin secretion in islets from GK rats does not simply result from a failure to close K(ATP) channels, nor does it result from an impairment in calcium secretion coupling.